PENGENALAN PROFESI APOTEKER DAN EDUKASI PENGENALAN BENTUK SEDIAAN OBAT SERTA PENGENALAN LOGO OBAT KEPADA SISWA/I DI SMA ST.PETRUS MEDAN - Evi Deviana Gultom (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Pharmacists are health workers who deal directly with the community. Drugs have a very important role in health services. Various drug options are currently being developed and available, so careful consideration is needed in choosing a drug to treat a disease. Public understanding of the pharmacist and medicine profession is not fully understood. For that outreach activities are needed. Students as a social component of society make a significant contribution to the development of the nation and are expected to be able to participate scientifically in accordance with their scientific disciplines. Therefore it is very important to carry out pharmacist branding from an early age, in this activity high school students will be educated. This training is intended to introduce the duties and functions of pharmacists, recognize drug dosage forms and introduce drug logos. This activity is carried out using the Socialization method, starting with reviewing the activity location, making an application letter and carrying out the activity. As for the implementation of the activity, namely first an explanation of the duties and functions of the Pharmacist Profession is carried out. Explanation of drugs, drug dosage forms, drug logos, how to use drugs. Selection of drugs and self-medication using medicines at home or those commonly obtained at the health facility. As for the results of the activity in the form of documentation at SMA St. Petrus Medan obtained. The students were very happy and focused on listening to the explanation of the material presented. The students will also be motivated by this activity because the pharmacist's role is very important in maintaining public health. Keyword : Pharmacists, drug dosage form, logo’s drug